2014
DOI: 10.1007/s10899-013-9437-y
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviour and Body Mass Index Among Problem Gamblers: Results from a Nationwide Survey

Abstract: Problem gambling is a serious public health issue. The objective of this study was to investigate whether past year problem gamblers differed from non-problem gamblers with regard to health behaviour and body mass index (BMI) among Danes aged 16 years or older. Data were derived from the Danish Health and Morbidity Surveys in 2005 and 2010. Past year problem gambling was defined using the lie/bet questionnaire. Logistic regression analyses were used to examine the association between past year problem gambling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 25 publications
5
23
3
Order By: Relevance
“…A higher BMI was associated with greater immediate gratification, and less value was placed on future rewards (Weller et al, 2008). These studies, along with research that connects BMI to impulsivity (e.g., Algren et al, 2015) and impulsivity to gambling (e.g., Blain et al, 2015;Vitaro et al,1999), provide support for a positive link between BMI and gambling, as observed from some of the gambling types in the current study. Previous research found that, compared with non-obese gamblers, obese gamblers are more likely to make more irrational choices because they are less able to moderate their risk taking (Grant et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…A higher BMI was associated with greater immediate gratification, and less value was placed on future rewards (Weller et al, 2008). These studies, along with research that connects BMI to impulsivity (e.g., Algren et al, 2015) and impulsivity to gambling (e.g., Blain et al, 2015;Vitaro et al,1999), provide support for a positive link between BMI and gambling, as observed from some of the gambling types in the current study. Previous research found that, compared with non-obese gamblers, obese gamblers are more likely to make more irrational choices because they are less able to moderate their risk taking (Grant et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…Hence, gambling may be an attractive choice for obese individuals, similar to the relationship between a sedentary lifestyle and obesity, especially TV watching (Johnson- Taylor & Everhart, 2006). A recent study by Algren et al (2015) also found that problem gamblers eat more unhealthily and are more likely to be obese than nonproblem gamblers. This may affect females more, given that previous studies tend to support the finding that females are less engaged in physical activities (Flintoff & Scraton, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Problem gambling is a public-health problem (Algren et al 2015; Griffiths 2004; Swedish Public Health Agency 2014), especially for adolescents and young adults (Messerlian et al 2005; Volberg et al 2010). Social and health costs of problem gambling are large both for societies and individuals (Griffiths 2004).…”
Section: Introductionmentioning
confidence: 99%